2018
DOI: 10.5465/ambpp.2018.13291abstract
|View full text |Cite
|
Sign up to set email alerts
|

The Dark Side of Interorganizational Relationships: An Integrative Review and Research Agenda

Abstract: General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.-Users may download and print one copy of any publication from the public portal for the purpose of private study or research-You may not further distribute the material or use it for any profit-making activity or commercia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
128
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(135 citation statements)
references
References 80 publications
5
128
0
2
Order By: Relevance
“…In addition, future researchers can distinguish the different stages of each SCM arrangement as a way to explore the process of opportunism manifestation across stages from partner selection, negotiation, implementation, and operation under that agreement. We envisage plentiful opportunities to study the temporal aspects (e.g., sequence and pace) in explicating opportunism (Oliveira & Lumineau, ).…”
Section: Further Topics For Researchmentioning
confidence: 99%
“…In addition, future researchers can distinguish the different stages of each SCM arrangement as a way to explore the process of opportunism manifestation across stages from partner selection, negotiation, implementation, and operation under that agreement. We envisage plentiful opportunities to study the temporal aspects (e.g., sequence and pace) in explicating opportunism (Oliveira & Lumineau, ).…”
Section: Further Topics For Researchmentioning
confidence: 99%
“…And not until recently did Ford Motor commit itself to the partnership with Changan by localizing its management team and offering more tested talents to product R&D, manufacturing, and marketing areas (Li 2018). In studying the failures of interorganizational relationships, Oliveira and Lumineau (2019) suggest that trust may backfire, and the extant literature mainly focuses on the inverted curvilinear effect of trust without a multiparty consideration of the effects of trust. By adopting a dyadic view to examine trust asymmetry, our study attempts to enrich the understanding of the dark side of trust.…”
mentioning
confidence: 99%
“…Second, despite abundant attention on the origins of trust, few studies explicitly consider how institutional factors influence trust asymmetry (for a review, see Table 1). Oliveira and Lumineau (2019) posit that a topic less studied in interorganizational relationships is how country-related antecedents influence interaction outcomes. For international exchange relationships, the distinct institutional backgrounds of interfirm partners may shape their attitudes and behaviors toward economic transactions and thus drive the level of trust asymmetry.…”
mentioning
confidence: 99%
“…Third, focusing solely on supplier attributes from an intraorganizational perspective fails to explain why generally positive characteristics of buyer–supplier relationships might also have negative effects. Recent research has emphasized that a dark side of long‐term and close buyer–supplier relationships exists (Oliveira & Lumineau, ). Studies have shown that close buyer–supplier relationships with excessive social capital can hurt the operational performance of those parties involved in the relationships (e.g., Anderson & Jap, ; Villena et al, ).…”
Section: Literature Reviewmentioning
confidence: 99%